Integrated carbonaceous honeycomb framework lithium metal composite negative electrode and preparation method thereof
Through the preparation of integrated carbon honeycomb structure materials, the problems of uneven lithium metal deposition and structural instability of existing three-dimensional carbon-based host materials in lithium-ion batteries are solved, and the stability and high lithium metal loading of high energy density lithium batteries are achieved.
Patent Information
- Application Number
- CN202510866561.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-09-23
AI Technical Summary
Existing three-dimensional carbon-based host materials have problems in lithium-ion batteries, such as ion transport kinetics hysteresis, local current density distortion, insufficient interfacial lithium affinity, and inactive components introduced by the preparation process, which lead to uneven lithium metal deposition and instability of the electrode structure, making it difficult to realize the application of high-energy-density lithium batteries.
Using an integrated carbon honeycomb structure material, through the preparation of metal salt-colloidal crystal microsphere template precursors, pressing molding and controllable carbonization technology, combined with lithium-philic modification and pore size optimization, a continuous three-dimensional ordered macroporous structure is formed, providing a fast ion and electron transmission path, and introducing lithium-philic functional groups into the lithium metal composite negative electrode to achieve uniform electric field distribution and dense deposition of lithium metal.
It achieves uniform deposition of lithium metal in the composite negative electrode, alleviates volume expansion, improves lithium metal loading and battery structure stability, and is suitable for the application of high energy density lithium batteries.
Smart Images

Figure HDA0005468712130000011 
Figure HDA0005468712130000021 
Figure HDA0005468712130000031
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium metal battery technology, specifically to a lithium metal composite anode based on an integrated carbon honeycomb architecture and its preparation method. This composite anode material has a three-dimensional ordered macroporous structure and is suitable for the construction of high-energy-density lithium batteries. Background Art
[0002] Currently, the energy density of lithium-ion batteries based on graphite anodes (theoretical lithium storage capacity: 372 mAh / g) has approached its theoretical limit. Lithium metal, due to its ultra-high theoretical specific capacity (3860 mAh / g), ultra-low redox potential (-3.04 V vs. SHE) and small density (0.534 g / cm 3 ) and other advantages, becoming the core material for building the next generation of high energy density lithium batteries.
[0003] Three-dimensional porous host materials have become a key strategy to solve the above problems by synergistically suppressing dendrites and alleviating volume changes through physical confinement and chemical regulation. Among them, although the three-dimensional metal-based host can provide mechanical support, its large deadweight reduces the overall energy density of the battery. In comparison, the three-dimensional carbon-based host has attracted much attention due to its advantages such as lightweight, adjustable pore size and chemical stability. Its large specific surface area can reduce the local current density, and the conductive skeleton can achieve rapid electron transfer, ion transport and uniform electric field distribution, thereby achieving dendrite-free homogeneous deposition of lithium metal; the adjustable pore structure provides space for the deposition of lithium metal and alleviates the volume expansion during the deposition / stripping process. However, the existing carbon-based hosts still face multiple challenges: First, the discontinuous porous structure leads to hysteresis in ion transport kinetics, causing local current density distortion in thick electrodes (>100μm), and the insufficient interfacial lithium affinity exacerbates the unevenness of lithium deposition; second, the inactive components such as binders introduced by the wet preparation process reduce the energy density of the electrode, and the lithium ion battery is not uniformly distributed at high surface capacity (>10mAh / cm 2 ) working conditions, spatial concentration polarization induces lithium deposition kinetics mismatch, aggravating structural instability and capacity decay.
[0004] Although strategies such as host topology design and interface chemistry regulation can effectively alleviate the above problems, the various three-dimensional hosts currently proposed (such as graphene layers and polymer-based porous materials) are mostly random network structures, lacking ordered structures and lithium-philic site design, and the preparation process is complex. In this regard, the inventor team developed a graphene-like carbon material with a three-dimensional ordered macroporous structure in previous research (patent number: CN201610565108.4). Based on this, through the preparation of metal salt-colloidal microsphere template precursors, compression molding, and calcination carbonization processes, the inventor team further developed an integrated integrated carbon honeycomb architecture material (patent number: CN202410323102.0). This material has structural advantages such as large geometric size, regular shape, highly ordered interconnected three-dimensional conductive network, high porosity, and large specific surface area, making it an ideal lithium metal anode host. This material can not only effectively reduce the local current density and provide space for lithium metal deposition, but also significantly alleviate volume expansion during the cycle. Based on the above structure-activity relationship, this host is expected to form a high-performance composite anode with lithium metal. To date, such an integrated lithium-carbon composite anode and its application in lithium metal batteries have not been reported in the literature or patents. Summary of the Invention
[0005] The purpose of the present invention is to provide a lithium metal composite negative electrode based on an integrated carbon honeycomb architecture. Among them, the integrated carbon honeycomb architecture host is prepared by optimizing the metal salt-colloidal microsphere template precursor preparation, compression molding and controllable carbonization technology (patent number: CN202410323102.0) developed by the inventor's team in the early stage, combined with lithium-philic modification, pore size optimization and other strategies. The host has a continuous three-dimensional ordered macroporous structure, which can provide a fast ion and electron transmission path and a uniform electric field distribution; a large specific surface area and uniform lithium-philic sites can reduce the local current density and induce dense deposition of lithium metal; a large pore volume and a stable integrated structure are helpful to achieve ultra-high capacity lithium metal loading and alleviate its volume change. Furthermore, using the integrated carbon honeycomb architecture material as a host, the target lithium metal composite negative electrode can be prepared by electrochemical deposition or lithium metal melting method.
[0006] The present invention provides a method for preparing a lithium metal composite negative electrode based on an integrated carbon honeycomb structure, comprising the following steps:
[0007] (1) immersing an organic colloidal microsphere template (such as PMMA microspheres, preferably ordered PMMA microspheres) in a mixed solution of zinc nitrate and citric acid, and drying to obtain a primary precursor; then pressing the precursor into a shape to obtain a bulk precursor;
[0008] (2) The obtained bulk precursor is placed in an inert atmosphere and carbonized at a certain temperature (>700°C) for 30 minutes to form a stable and highly conductive three-dimensional skeleton to obtain an integrated carbon honeycomb structure material;
[0009] (3) placing the integrated carbon honeycomb structure material in step (2) in an air atmosphere and performing an oxidation treatment at a certain temperature (<500° C.) to introduce lithium-philic functional groups (such as -COOH, -OH, -COOR) to improve its interfacial affinity with lithium metal;
[0010] (4) depositing lithium metal in the three-dimensional ordered macropores of the integrated carbon honeycomb structure host obtained in step (2) or step (3) by electrochemical deposition to form an integrated lithium metal composite structure; or co-pressing the lithium metal sheet and the obtained carbonaceous host in a vacuum or inert atmosphere and heating them to a temperature higher than the melting point of lithium metal, so that the lithium metal diffuses and fills in its macroporous structure, and after cooling, an integrated composite structure in which the lithium metal and the carbon skeleton are tightly combined is formed.
[0011] Preferably, the ratio of zinc nitrate to citric acid in step (1) is 2:1; the diameter of the PMMA microsphere template is 100-1000 nm; and the applied pressure is 6-8 MPa;
[0012] Preferably, the carbonization temperature in step (2) is 800–1200°C, the heating rate is 4°C / min, and the holding time is 30 min;
[0013] Preferably, the oxidation temperature in step (3) is 300–500° C. and the time is 0–6 h;
[0014] Preferably, the current density of the electrochemical deposition method in step (4) is 0.05–5 mA / cm 2 , deposition capacity of 2–50 mAh / cm 2 The electrolyte is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; 1 mol / L) dissolved in a mixed solvent of ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) (DME / DOL volume ratio is 1:1) with 2% LiNO3 added;
[0015] Preferably, the melting temperature of the molten lithium diffusion method in step (4) is 200-350°C, the heating time is 5-60 min, and the pressure is 1-10 MPa.
[0016] Step (4) ultimately enables the lithium metal in the integrated composite structure to be filled into the macroporous structure of the host.
[0017] Further using the integrated carbon honeycomb structure host of step (3) can further increase the lithium loading capacity while making the surface deposition smoother, more uniform and denser.
[0018] The preparation method provided by the present invention has the following advantages:
[0019] (a) The carbonaceous host prepared by steps (1) and (2) can form a stable and integrated ordered macroporous network, achieve rapid electron transfer and ion transport, and uniform electric field distribution. The macroporous volume provides space for lithium metal deposition, which helps to alleviate volume expansion;
[0020] (b) introducing lithiophilic functional groups through oxidation treatment to enhance the interfacial affinity between carbonaceous materials and lithium metal, induce uniform internal deposition of lithium metal, and reduce dendrite formation;
[0021] (c) By adjusting parameters such as PMMA microsphere particle size, pressing pressure, and carbonization temperature, the thickness and pore structure of the electrode can be flexibly controlled to meet requirements such as high capacity and high power.
[0022] (d) The controllable deposition of lithium metal can be achieved through electrochemical deposition, and the efficient and low-energy deposition process can be achieved through molten lithium diffusion, which is suitable for different application scenarios;
[0023] (e) The prepared lithium metal composite anode exhibits excellent structural stability over multiple cycles, significantly extending the battery life and is suitable for high energy density lithium battery systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] To more clearly illustrate the embodiments of the present invention and the technical solutions in the prior art, the following briefly introduces the relevant drawings. Obviously, the drawings are for illustrative purposes only, and those skilled in the art can derive other relevant schematic diagrams based on the drawings without inventive effort.
[0025] Figure 1 is the cross section of the integrated carbon honeycomb structure host material prepared in Examples 1-5 and Comparative Example 1 ( Figure 1 a, c, e, g, i, k) and plane ( Figure 1 b, d, f, h, j, l) SEM images used to characterize the structural integrity and pore size distribution of the material.
[0026] Figure 2 The cross section of the integrated carbon honeycomb structure lithium metal composite negative electrode (samples 2-5 and comparative sample 1) prepared in Examples 2-5 and Comparative Example 1 ( Figure 2 a, c, e, g, i) and plane ( Figure 2 b, d, f, h, j) SEM images used to analyze the uniformity and structural stability of lithium deposition.
[0027] Figure 3is the cross section of the integrated carbon honeycomb structure lithium metal composite negative electrode (sample 6) obtained in Example 6 ( Figure 3 a) and plane ( Figure 3 b) SEM image, the inset is an optical photograph of the sample, used to demonstrate the deposition morphology under high areal capacity.
[0028] Figure 4 It is the cycle performance of the symmetrical battery based on samples 1-5 and comparative sample 1 in Example 7, which is used to compare the cycle life and stability of different samples. DETAILED DESCRIPTION
[0029] The following describes the specific embodiments of the present invention in detail with reference to the accompanying drawings and examples. However, these embodiments should not be considered as limiting the scope of protection of the present invention. Any improvement scheme based on the teachings of the present invention or combined with the prior art should be considered within the scope of protection of the present invention.
[0030] The specific operation methods and test methods used in the present invention are conventional methods in the field. Unless otherwise specified, the conventional experimental operations or conditions described in the literature in the field can be followed. The reagents involved in the present invention are all existing conventional commercial products.
[0031] All batteries in the following examples of the present invention (including batteries for lithium electrodeposition) are assembled according to the following method: (i) in a glove box filled with argon protection (H2O <0.5ppm and O2 <0.5ppm); (ii) the electrolyte is LiTFSI (concentration is 1 mol / L) dissolved in a mixed solvent of DME and DOL with a volume ratio of 1:1 and containing 2% LiNO3 additive; (iii) polypropylene (PP) or glass fiber is used as the separator; (iv) the positive electrode shell, positive electrode and separator are placed in sequence, and after the electrolyte is added, the negative electrode, gasket, spring sheet and negative electrode shell are placed, and finally the package is packaged using a hydraulic press.
[0032] Example 1
[0033] First, an ordered PMMA microsphere template with a particle size of 370nm was immersed in a mixed solution of zinc nitrate and citric acid in a molar ratio of 2:1, and a primary precursor was obtained after drying. Subsequently, 120mg of the precursor was placed in a cylindrical mold and pressed at a pressure of 6MPa for 30s to form a bulk precursor. Next, the bulk precursor was heated to 800℃ at a heating rate of 4℃ / min in a tube furnace in an inert atmosphere (such as argon), kept warm for 30min, and then cooled to room temperature to obtain an integrated carbon honeycomb structure material with a three-dimensional ordered macroporous structure. The thickness was about 345μm and the pore size was about 225nm. Finally, a button battery was assembled with this material as the positive electrode and lithium metal as the negative electrode, and a constant current method was used at 0.2mA / cm 2Deposition at a current density of 10 mAh / cm 2 of lithium metal to form an integrated lithium metal composite negative electrode (sample 1). SEM image ( Figure 1 Figures (a) and (b) show that the obtained material has uniform thickness, regular structure, and a highly interconnected conductive skeleton.
[0034] Example 2
[0035] First, an ordered PMMA microsphere template with a particle size of 370 nm was immersed in a mixed solution of zinc nitrate and citric acid in a molar ratio of 2:1, and dried to obtain a primary precursor. Subsequently, 120 mg of the precursor was placed in a cylindrical mold and pressed at a pressure of 6 MPa for 30 seconds to form a bulk precursor. The bulk precursor was then heated to 1100 ° C at a heating rate of 4 ° C / min in a tube furnace under an inert atmosphere (such as argon), kept at this temperature for 30 minutes, and then cooled to room temperature to obtain an integrated carbon honeycomb structure material with a thickness of about 295 μm and a pore size of about 220 nm ( Figure 1 Finally, the obtained integrated carbon honeycomb structure material was used as the positive electrode and the lithium metal sheet was used as the negative electrode to assemble a button-type battery. The battery was then charged at 0.2 mA / cm 2 Lithium metal was deposited at a current density of 10 mAh / cm 2 , and obtain an integrated carbon honeycomb structure lithium metal composite negative electrode (sample 2). Cross-sectional SEM image ( Figure 2 Middle a) shows that the thickness of sample 2 is uniform, about 302 μm, and no obvious lithium metal deposition is observed on the upper surface; the surface SEM image ( Figure 2 Figure b) shows that lithium metal is evenly filled in the three-dimensional ordered macroporous structure, forming a relatively smooth and dense deposition layer. The overall volume loading of lithium metal in sample 2 is calculated to be approximately 312.5 mAh / cm 3 .
[0036] Example 3
[0037] First, the integrated carbon honeycomb structure material obtained in Example 2 was placed in a muffle furnace and oxidized at 350 ° C for 3 h in an air atmosphere to introduce surface oxygen-containing functional groups to enhance the lithiophilicity of the material, thereby obtaining a lithiophilic-modified integrated carbon host material ( Figure 1 Then, the lithium-philic modified integrated carbon honeycomb structure material was used as the positive electrode and the lithium metal sheet was used as the negative electrode to assemble a button-type battery; finally, a constant current method was used to 2 Lithium metal was deposited at a current density of 10 mAh / cm 2 , thus obtaining an integrated carbon honeycomb structure lithium metal composite negative electrode (sample 3). Cross-sectional SEM image ( Figure 2(c) shows that the thickness of sample 3 is about 290 μm, and no obvious lithium metal deposition layer is observed on the surface; while the surface SEM image ( Figure 2 d) shows that lithium metal is uniformly filled in the three-dimensional ordered macroporous structure, and compared with sample 2, the surface deposition is smoother, more uniform and dense, showing better deposition induction ability. The overall volume loading of lithium metal in this sample is about 344.8 mAh / cm 3 , which is improved compared with sample 2.
[0038] Comparative Example 1
[0039] First, zinc nitrate and citric acid were prepared into a mixed solution at a molar ratio of 2:1, impregnated into a disordered PMMA template (spherical diameter 370nm), fully infiltrated and dried to obtain a primary precursor. 120mg of the precursor was taken and pressed in a cylindrical mold at a pressure of 6MPa for 30s to form a bulk precursor; secondly, the obtained bulk precursor was placed in a tube furnace in an inert atmosphere (such as argon) and heated to 1100℃ at a heating rate of 4℃ / min. After keeping warm for 30min, it was cooled to room temperature to obtain an integrated carbon honeycomb structure material with a thickness of about 300μm and a pore size of about 220nm ( Figure 1 g, h); then, the above materials were placed in a muffle furnace and oxidized at 350°C for 3 hours in an air atmosphere to introduce surface oxygen-containing functional groups to obtain a lithium-philic modified integrated host material; finally, the lithium-philic modified integrated carbon honeycomb structure material was used as the positive electrode and the lithium metal sheet was used as the negative electrode to assemble a button-type battery. Using a constant current method, the battery was heated at 0.2 mA / cm 2 Deposition at a current density of 10 mAh / cm 2 The lithium metal was used to prepare an integrated carbon honeycomb structure lithium metal composite negative electrode (comparative sample 1). Cross-sectional SEM image ( Figure 2 (e) shows that the thickness of comparative sample 1 is about 340 μm, of which about 35 μm of lithium metal is deposited on the surface of the material, indicating that its internal structure fails to effectively guide the deposition of lithium metal; the surface SEM image ( Figure 2 Figure f) shows that although the three-dimensional macroporous structure is filled, the lithium metal deposition is unevenly distributed, with local accumulation and structural discontinuity. Compared with samples 2 and 3, the deposition behavior of this sample is poor, and its overall volumetric lithium metal loading is approximately 294.1 mAh / cm 3 , which is significantly lower than that of samples 2 and 3.
[0040] Example 4
[0041] First, zinc nitrate and citric acid were prepared into a mixed solution at a molar ratio of 2:1, which was fully impregnated into an ordered PMMA microsphere template (sphere diameter 170nm) and dried to obtain a primary precursor; 80mg of the precursor was taken and pressed in a cylindrical mold at a pressure of 8MPa for 30s to form a bulk precursor. Secondly, the obtained bulk precursor was placed in a tube furnace in an inert atmosphere (such as argon) and heated to 1100℃ at a heating rate of 4℃ / min. After keeping warm for 30min, it was naturally cooled to room temperature to obtain an integrated carbon honeycomb structure material with a thickness of about 208μm and a pore size of about 100nm ( Figure 1 i and j). Again, the obtained integrated carbon honeycomb structure material was used as the positive electrode and the lithium metal sheet was used as the negative electrode to assemble a button-type battery; finally, a constant current method was used to 2 Lithium metal was deposited at a current density of 10 mAh / cm 2 , thus obtaining an integrated carbon honeycomb structure lithium metal composite negative electrode (sample 4). Cross-sectional SEM image ( Figure 2 Middle g) shows that the thickness of sample 4 is about 225 μm, and no obvious lithium metal deposition layer is observed on the surface, indicating that the lithium metal is mainly deposited inside the three-dimensional macroporous structure; the surface SEM image ( Figure 2 Figure h) shows that lithium metal is evenly filled in the structure, forming a smooth and dense deposition layer, showing good deposition consistency. The overall volume loading of lithium metal in sample 4 was determined to be approximately 444.4 mAh / cm 3 .
[0042] Example 5
[0043] First, zinc nitrate and citric acid were prepared into a mixed solution at a molar ratio of 2:1, fully immersed in an ordered PMMA microsphere template (sphere diameter 905nm), and dried to obtain a primary precursor. Take 80mg of the precursor and press it in a cylindrical mold at a pressure of 8MPa for 30s to form a block precursor. Secondly, the block precursor was placed in a tubular furnace in an inert atmosphere (such as argon), heated to 1100℃ at a heating rate of 4℃ / min, kept warm for 30min, and then naturally cooled to room temperature to obtain an integrated carbon honeycomb structure material with a thickness of about 185μm and a pore size of about 480nm ( Figure 1 k and l). Again, the integrated carbon honeycomb structure material was used as the positive electrode and the lithium metal sheet was used as the negative electrode to assemble a button-type battery. Finally, a constant current method was used to 2 Lithium metal was deposited at a current density of 10 mAh / cm 2 , thus obtaining an integrated carbon honeycomb structure lithium metal composite negative electrode (sample 5). Cross-sectional SEM image ( Figure 2(i) shows that its thickness is about 200 μm and is evenly distributed. No obvious lithium metal deposition layer is seen on the surface, indicating that lithium metal is mainly uniformly deposited inside the three-dimensional macropores. Surface SEM image ( Figure 2 Figure j) shows that lithium metal is evenly filled in its macroporous structure, forming a smooth and dense deposition surface, further verifying the effective regulation of lithium deposition behavior by this structure. The overall volume loading of lithium metal in sample 5 was measured to be approximately 500 mAh / cm 3 , which is significantly better than samples 2-4 and comparative example 1.
[0044] Example 6
[0045] The lithium-philic modified host in Example 3 was used as the positive electrode and the lithium metal sheet was used as the negative electrode to assemble a button-type battery. 2 Deposition 50mAh / cm 2 of lithium metal to obtain sample 6. Cross-sectional SEM image ( Figure 3 (a) shows that its thickness is uniform, about 442 μm, and no obvious metal lithium deposition layer is observed on the surface, indicating that lithium metal is mainly deposited inside the three-dimensional ordered macroporous structure; the surface SEM image ( Figure 3 Figure b) shows that some lithium metal begins to deposit on the host surface in the form of blocks, with an average particle size of about 12.5μm, but no lithium dendrite growth occurs, indicating good structural stability and deposition uniformity. The overall volumetric loading of lithium metal in sample 6 is measured to be approximately 1093.7mAh / cm 3 , which is significantly improved compared with samples 2-5.
[0046] Example 7
[0047] Samples 1-5 and Comparative Example 1 (lithium deposition capacity is 10 mAh / cm 2 ) were assembled into symmetrical batteries (positive and negative electrodes were the same) and tested at 1 mA / cm 2 Current density, 1mAh / cm 2 Cycling stability under deposition-stripping capacity conditions. Figure 4 As shown in Figure a, sample 3 exhibits the highest cycling stability, with stable cycling for more than 1950 h (975 cycles). Figure 4 b shows that sample 5 (larger pore size) has better cycle life than sample 4 (smaller pore size), with stable cycling for more than 1200 h.
Claims
1. A method for preparing a lithium metal composite negative electrode based on an integrated carbon honeycomb structure, characterized in that: The steps include: (1) Immersing the organic colloidal microsphere template in a mixed solution of zinc nitrate and citric acid, and drying to obtain a primary precursor; then pressing the precursor into a shape to obtain a block precursor; (2) placing the obtained bulk precursor in an inert atmosphere and carbonizing it at a certain temperature >700°C for 30 min to form a stable and highly conductive three-dimensional skeleton to obtain an integrated carbon honeycomb structure material; (3) placing the integrated carbon honeycomb structure material in step (2) in an air atmosphere and performing an oxidation treatment at a certain temperature <500° C. to introduce lithium-philic functional groups and improve its interfacial affinity with lithium metal; (4) depositing lithium metal in the three-dimensional ordered macropores of the integrated carbon honeycomb structure host obtained in step (2) or step (3) by electrochemical deposition to form an integrated lithium metal composite structure; or co-pressing the lithium metal sheet and the obtained carbonaceous host in a vacuum or inert atmosphere and heating them to a temperature higher than the melting point of lithium metal, so that the lithium metal diffuses and fills in its macroporous structure, and after cooling, an integrated composite structure in which the lithium metal and the carbon skeleton are tightly combined is formed.
2. The method according to claim 1, characterized in that The ratio of zinc nitrate to citric acid in step (1) is 2:1; the diameter of the PMMA microsphere template (preferably ordered) is 100-1000 nm; and the applied pressure is 6-8 MPa.
3. The method according to claim 1, characterized in that The carbonization temperature in step (2) is 800–1200°C, the heating rate is 4°C / min, and the holding time is 30 min.
4. The method according to claim 1, characterized in that The oxidation temperature in step (3) is 300–500°C and the time is 0–6 h.
5. The method according to claim 1, characterized in that The current density of the electrochemical deposition method in step (4) is 0.05–5 mA / cm 2 , deposition capacity of 2–50 mAh / cm 2 The electrolyte is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; 1 mol / L) dissolved in a mixed solvent of ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) (DME / DOL volume ratio is 1:1) with the addition of 2% LiNO3.
6. The method according to claim 1, characterized in that The melting temperature of the molten lithium diffusion method in step (4) is 200-350°C, the heating time is 5-60 minutes, and the pressure is 1-10 MPa.
7. The method according to claim 1, characterized in that Step (4) ultimately enables the lithium metal in the integrated composite structure to be filled into the macroporous structure of the host.
8. The method according to claim 1, characterized in that The integrated carbon honeycomb structure host using step (3) can further increase the lithium loading capacity while making the surface deposition smoother, more uniform and dense.
9. A lithium metal composite negative electrode prepared according to the method according to any one of claims 1 to 8.
10. Use of the lithium metal composite negative electrode prepared by the method according to any one of claims 1 to 8 as a negative electrode for lithium batteries.
Citation Information
Patent Citations
Three-dimensional ordered macroporous-structured graphene-like carbon material, preparation method and application therefor
CN106129410A
Integrated carbonaceous honeycomb framework material and preparation method thereof
CN118125836A
Cited By
All-solid-state lithium battery based on carbonaceous honeycomb framework and in-situ polyelectrolyte
CN122202461A
Sodium metal composite negative electrode based on integrated carbonaceous honeycomb architecture and preparation method thereof
CN122455763A
A carbonaceous honeycomb architecture integrated with an in-situ polymerized fluorinated electrolyte solid state electrode
CN122511841A
A vertically gradient-pore carbonaceous honeycomb architecture material used as a lithium metal host
CN122540841A